Pengembangan media pembelajaran berbasis android berbantuan smart apps creator untuk mengeksplor kemampuan berpikir kritis peserta didik - Putriyannah, Lia Nur Indah; Ratnaningsih, Nani; Rahayu, Diar Veni (IKIP Siliwangi, 2025)
This study was driven by the challenges students face in understanding polyhedra, particularly when relating concepts to real-world contexts and solving problems that demand critical thinking. The research aimed to outline the development stages and evaluate the effectiveness of an Android-based learning medium created using Smart Apps Creator to enhance students’ critical thinking skills. Participants included two subject matter experts, two media experts, three teachers, and 32 eighth-grade students from SMP Negeri 20 Tasikmalaya. The study applied a Research and Development approach following the ADDIE model. Data were collected through observations, interviews, tests, and questionnaires, using instruments such as critical thinking tests, expert validation sheets, and user response surveys. Findings showed that teacher and student responses were categorized as excellent, and the effect size test yielded a value of 2.8 (strong effect). This research is expected to contribute theoretically to the development of technology-enhanced learning media and provide a practical, innovative alternative for teachers to deliver polyhedra lessons interactively, engagingly, and contextually.